1999
DOI: 10.1152/jn.1999.82.5.2786
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Muscle Movement on Two Time Scales by a Sensory Neuron That Switches Between Spiking and Bursting Modes

Abstract: The gastropyloric receptor (GPR) neurons of the stomatogastric nervous system of the crab Cancer borealis are muscle stretch receptors that can fire in either a spiking or a bursting mode of operation. Our goal is to understand what features of muscle stretch are encoded by these two modes of activity. To this end, we characterized the responses of the GPR neurons in both states to sustained and rapidly varying imposed stretches. The firing rates of spiking GPR neurons in response to rapidly varying stretches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
(16 reference statements)
2
38
0
Order By: Relevance
“…In a previous immunocytochemical study, there were a maximum of six FLRFamide-positive neurons, identified as GPR neurons, found in the embryonic, larval, and adult lvn posterior to the gastric mill muscles of H. americanus and gammarus . Thus, we conclude that the stained neurons in the present paper are the embryonic and adult GPR neurons, already characterized using either immunocytochemichal (Beltz et al, 1984;Turrigiano and Selverston, 1991;Kilman et al, 1999;Skiebe, 1999) or electrophysiological Birmingham et al, 1999) techniques. Therefore, our data indicate that GPR cells are already present at developmental stage 65% and that they express the same pattern of projection as in the adult.…”
Section: Neurons In the Periphery That Project To The Stgsupporting
confidence: 66%
“…In a previous immunocytochemical study, there were a maximum of six FLRFamide-positive neurons, identified as GPR neurons, found in the embryonic, larval, and adult lvn posterior to the gastric mill muscles of H. americanus and gammarus . Thus, we conclude that the stained neurons in the present paper are the embryonic and adult GPR neurons, already characterized using either immunocytochemichal (Beltz et al, 1984;Turrigiano and Selverston, 1991;Kilman et al, 1999;Skiebe, 1999) or electrophysiological Birmingham et al, 1999) techniques. Therefore, our data indicate that GPR cells are already present at developmental stage 65% and that they express the same pattern of projection as in the adult.…”
Section: Neurons In the Periphery That Project To The Stgsupporting
confidence: 66%
“…Our approach is likely to approximate events occurring in the feeding animal because the VCN neurons are thought to be activated during stomach distention , and the VCN-triggered chewing motor pattern would involve rhythmic stretch of the GPR-innervated muscles. Under some conditions, however, GPR either exhibits a modest activation during the protractor phase or is spontaneously rhythmic Birmingham et al, 1999). We did not study these situations, but our results suggest that GPR activation during the protractor phase would have, at most, a small impact on the gastric mill rhythm, because at this time MCN1 receives strong presynaptic inhibition from the LG neuron .…”
Section: Sensory Regulation Of Neural Circuit Activitymentioning
confidence: 75%
“…This experimental approach has led to an improved understanding, albeit not yet at the level of identified circuit neurons, of phasic sensory influence on both intralimb and interlimb coordination during locomotion (Pearson, 2004;Buschges, 2005). We therefore recapitulated a behaviorally relevant scenario for the GPR neurons by replicating their previously documented response to stretch of the muscles in which their dendrites are embedded Birmingham et al, 1999). Our approach is likely to approximate events occurring in the feeding animal because the VCN neurons are thought to be activated during stomach distention , and the VCN-triggered chewing motor pattern would involve rhythmic stretch of the GPR-innervated muscles.…”
Section: Sensory Regulation Of Neural Circuit Activitymentioning
confidence: 98%
“…Therefore, GPR was stimulated rhythmically to reflect this range of periods. GPR1/2 often are activated at relatively low firing frequencies (Ͻ10 Hz) in response to stretch of the gastric mill muscles they innervate (Katz and HarrisWarrick, 1989;Birmingham et al, 1999). Therefore, we used a steady intraburst stimulus rate (5 Hz) that was within its previously reported range.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we used a steady intraburst stimulus rate (5 Hz) that was within its previously reported range. The stimulus duration that was used for each GPR stimulus (4 sec) reflected the previously described gastric mill-timed burst duration of the motor neuron (dorsal gastric, DG) that causes the GPR-innervated muscles to stretch Birmingham et al, 1999;. Thus the standard GPR stimulation parameters used in this study included burst durations of 4 sec, an intraburst firing frequency of 5 Hz, and a cycle period range of 8 -50 sec.…”
Section: Methodsmentioning
confidence: 99%